Photochemistry, history and commercial applications of hexaarylbiimidazoles : all about HABIs - Dessauer, Rolf (Elsevier, 2006)
The objective of this book is to acquaint the reader with a novel class of photochemical oxidants and polymerization initiators that have become widely accepted in industry. As most of the work with these materials is reported in the patent literature, an effort has been made to study this area of scientific activity, as well as present a thorough review of the journal publications. Photochemistry, History and Commercial Applications of HABIs also presents new technologies such as waveguides, holography along with some more traditional applications (i.e. filters, litho plates, and photoresists). * A complete review of technology associated with hexaarylbiimidazoles * Includes CDs with spreadsheets describing the patents and journal references * Includes DVDs containing interviews with inventors of the technology.